Modern warfarin- dosing algorithms in patients with atrial fibrillation - M. Yu. Kolesnyk; Ya. M. Mykhaylovskyi (Zaporožskij Medicinskij Žurnal)
Aim. Thromboembolic complications are the leading cause of mortality in patients with atrial fibrillation. In order to summarize and represent a modern view on the anticoagulation therapy with warfarin recent specialized literature was reviewed. It was found that warfarin therapy is characterized by some difficulties in applying that limit the frequency of its appointment in patients with atrial fibrillation. It was found that the metabolism of warfarin is influenced by many factors, among which important role is given to genetic factors.